2020
DOI: 10.1111/iar.12337
|View full text |Cite
|
Sign up to set email alerts
|

Variations in trace elements, isotopes, and organic geochemistry during the Hangenberg Crisis, Devonian–Carboniferous transition, northeastern Vietnam

Abstract: The Hangenberg Crisis at the Devonian-Carboniferous boundary is known as a polyphase extinction event that affected more than 45 % of marine and terrestrial genera. As the cause of this event is still debated, analyses were carried out on sedimentary samples from the Devonian-Carboniferous Pho Han Formation in northeastern Vietnam to reconstruct the paleoenvironment around the time of this event using stable carbon isotopes; total sulfur; manganese; vanadium; molybdenum; and sedimentary organic matter, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
(212 reference statements)
0
5
0
Order By: Relevance
“…Geochemical studies (trace element proxies, total organic carbon, framboidal pyrite distributions, etc.) and a significant mercury enrichment suggest dysoxic/ anoxic conditions from the latest Famennian through the early Tournaisian with severe anoxia (approaching euxinia) throughout the Hangenberg Event interval (Paschall et al 2019;Shizuya et al 2020). The authors interpret the mercury anomaly as the result of large-scale volcanic activity.…”
Section: Vietnammentioning
confidence: 93%
See 3 more Smart Citations
“…Geochemical studies (trace element proxies, total organic carbon, framboidal pyrite distributions, etc.) and a significant mercury enrichment suggest dysoxic/ anoxic conditions from the latest Famennian through the early Tournaisian with severe anoxia (approaching euxinia) throughout the Hangenberg Event interval (Paschall et al 2019;Shizuya et al 2020). The authors interpret the mercury anomaly as the result of large-scale volcanic activity.…”
Section: Vietnammentioning
confidence: 93%
“…The Cat Co section, located in the Cat Ba Island (northwestern Vietnam) and exposing rocks of the Pho Han Formation, has been studied in detail in the recent period with multidisciplinary studies including conodont biostratigraphy, facies analysis, trace elements, isotopes and organic geochemistry (Komatsu et al 2012(Komatsu et al , 2014Paschall et al 2019;Shizuya et al 2020). The section (Fig.…”
Section: Vietnammentioning
confidence: 99%
See 2 more Smart Citations
“…2). However, there is still debate about the cause/effect relationship between anoxia and extinction in the Devonian (Bratton et al 1999;Copper 2002;Joachimski and Buggisch 2002;George et al 2014;Shizuya et al 2019;Aretz 2021), as the epeiric seas and tectonic basins of eastern North America and Europe generally show a close association between the two (Bond and Wignall 2009 and references therein) but sites elsewhere (particularly in Australia) do not (Becker et al 1991;Bratton et al 1999;George et al 2014;. Others have suggested that climate cooling rather than anoxia was the cause of the mass extinction (Copper 1986;Joachimski and Buggisch 2002;Huang et al 2018).…”
Section: State Of the Artmentioning
confidence: 99%